ANALYZING GENSHIN IMPACT PLAYER BEHAVIOR FOR STRATEGIC DEVELOPMENT IN THE GAMING INDUSTRY - Rochelle, Jessenia Nadea; Rumokoy, Lawren Julio; Gunawan, Emilia Margareth (Universitas Sam Ratulangi, 2025)
This study aims to analyse the online game player of Genshin Impact, one of the popular cross platforms online games and to analyse also a strategic development for gaming industry based on the player behaviour. The variable in this study is Consumer Behaviour. This research uses a qualitative method with a sample of 15 Genshin Impact players in Manado that already played the game for minimum 2 months. Data was collected through face to face in depth interview. The results of this study indicate that based on player’s preference, enjoyment and satisfaction can build a certain behaviour when playing the game also have an impact to player’s long term gaming engagement. A company also can make a strategy based on player’s preference, enjoyment and satisfaction so the player may stay to play the game for a long term of time. Keywords: Consumer Behaviour